Cultivating Vitality: Unveiling the Transformative Effects of Exercise on Menopausal Women's Well-being and Physiological Markers: A Meta-Analysis of Randomized Control Trial - Alfredo Wijaya; Alifian Singgih Fachrani; Gloria Claudia Kastanja; Indy Zahrotul Firdaus; Muhammad Rifky Alif Syahputra (Asian Journal of Health Research, 2024)
Introduction: Menopause frequently coincides with age-related hormonal decline, elevated blood pressure, and unfavorable body composition changes, collectively heightening the risk of cardiovascular disease. Addressing the adverse effects of menopause is crucial through the integration of suitable lifestyle interventions, such as exercise. Nonetheless, there remains controversy within studies regarding the significance of exercise in improving Quality of Life (QoL), reducing Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), Total Cholesterol (TC), and Low-Density Lipoprotein (LDL), as well as maintaining Bone Mineral Density (BMD). Thus, this review aims to determine and clarify the influence of exercise on patient outcomes. Materials/Methods: This meta-analysis followed the PRISMA statement guidelines, utilizing databases such as PubMed, ScienceDirect, and Google Scholar over the past ten years. Inclusion criteria adhered to the PICOS framework, and the literature quality assessment was based on the Risk of Bias 2.0 Tool. Results: Out of 14 included studies, the majority indicated no significant improvements in menopause women undergoing exercise regarding QoL [MD: -6.62 (95% CI: -16.90 – -3.66, I2=91%)], SBP [MD: -4.74 (95% CI: -10.54 – 1.05, I2=100%)], DBP [MD: -4.52 (95% CI: -8.59 – -0.46, I2=99%)], TC [MD: -4.06 (95% CI: -8.75 –0.64, I2=57%)], LDL [MD: -2.26 (95% CI: -7.37 – 2.86, I2=65%)], and BMD [MD: 0.06 (95% CI: -0.01 – 0.13, I2=86%)]. Significant improvements were seen only in DBP outcomes Conclusion: Menopause exercise women may effectively raise QoL, reduce SBP, DBP, TC, and LDL, also maintain BMD.